KOMPETENSI GURU PENDIDIKAN JASMANI DALAMMENINGKATKAN HASIL BELAJAR SISWA DI MASA COVID - 19 - Sigit Permadi, (2022)
Penelitian ini bertujuan untuk mengetahui: (1) Korelasi kompetensi guru pendidikan jasmani dalam meningkatan hasil belajar aspek afektif, (2) Korelasi kompetensi guru pendidikan jasmani dalam meningkatan hasil belajar aspek kognitif, (3) Korelasi kompetensi guru pendidikan jasmani dalam meningkatan hasil belajar aspek psikomotor. Subjek penelitian ini adalah siswa SMAN Tanjungsari yang sebanyak 192 siswa. Metode penelitian yang digunakan yaitu studi korelasional dengan desain penelitian menggunakan korelasi pearson. Instrumen yang digunakan untuk mengukur kompetensi guru yaitu menggunakan kuisioner. Hasil peneltian yang di dapatkan yaitu terdapat hubungan antara kompetensi guru pendidikan jasmani dalam meningkatkan hasil belajar pada aspek afektif masa pandemi covid-19 dengan nilai r hitung lebih besar dari r tabel (0,213 > 0,141). Kemudian terdapat hubungan antara kompetensi guru pendidikan jasmani dalam meningkatkan hasil belajar pada aspek kognitif masa pandemi covid-19 dengan nilai r hitung lebih besar dari r tabel (0,611 > 0,141). Dan terdapat hubungan antara kompetensi guru pendidikan jasmani dalam meningkatkan hasil belajar pada aspek psikomotor masa pandemi covid-19 dengan r hitung lebih besar dari r tabel (0,615 > 0,141) maka dapat disimpulkan bahwa terdapat korelasi antara kompetensi guru pendidikan jasmani dalam meningkatkan hasil belajar siswa aspek afektif, kognitif, psikomotor. This study aims to determine: (1) The correlation of the competence of physical education teachers in increasing learning outcomes in the affective aspect, (2) The correlation of the competence of physical education teachers in increasing learning outcomes in the cognitive aspect, (3) The correlation of the competence of physical education teachers in increasing learning outcomes in the psychomotor aspect . The subjects of this research were 192 students of Tanjungsari High School. The research method used is a correlational study with a research design using Pearson's correlation. The instrument used to measure teacher competency is using a questionnaire. The research results obtained are that there is a relationship between the competence of physical education teachers in improving learning outcomes in the affective aspect during the Covid19 pandemic with an r count value greater than r table (0.213 > 0.141). Then there is a relationship between the competence of physical education teachers in improving learning outcomes in cognitive aspects during the Covid-19 pandemic with an r count value greater than r table (0.611 > 0.141). And there is a relationship between the competence of physical education teachers in improving learning outcomes in the psychomotor aspect during the Covid-19 pandemic with r count greater than r table (0.615 > 0.141). It can be concluded that there is a correlation between the competence of physical education teachers in improving student learning outcomes in aspects affective, cognitive, psychomotor.